Sustainable development in practice sustainomics methodology and applications - Munasinghe, Mohan, 1945- (Munasinghe Institute for Development (MIND) series on growth and sustainable development., 2009)
This text provides a practical analysis of sustainable development prospects today by applying the innovative sustainomics framework. It illustrates the methodology with empirical case studies that are practical and policy-relevant over a range of time and geographic scales, countries, sectors, ecosystems and circumstances.